The Influence of Profitability and Leverage on Firm Value with Firm Size as A Moderation Variable - Raditya Hanan Naufal Hardiyanto; Akhmadi Akhmadi (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This research aims to analyze the effect of profitability and leverage on Firm Value with Firm size as a moderating variable in sector companies with processed food sub-industry listed on the Indonesia Stock Exchange in 2021 - 2023. The sample and population in this study consist of 19 companies Processed Food Sub Industry. The data analysis method used in this research is panel data regression analysis and regression analysis with moderate data processing carried out by this research using SPSS Statistics 27 software. The results of the research show that all variables pass the classical assumption test and are suitable for use as research data. The t test statistic on Firm value shows that profitability has a positive but not significant effect on Firm value, while leverage does not have a significant effect on Firm value. Firm size is able to moderate profitability and leverage on Firm value.